Monocytes and Fibrinogen as Biomarkers in Type 2 Diabetes Mellitus - Michela Crisci; Fabiana Flagiello; Giovanni Lepore; Federica Feleppa; Alessandro Crisci (International Journal of Medical Science and Clinical Research Studies, 2024)
Background: In the diagnosis of diabetic foot, in addition to the inflammatory biomarkers that have been widely interested and used, for example procalcitonin, C-reactive protein (CRP), ESR, leukocyte count, neutrophil count, Fibrinogen and Monocytes are considered as biomarkers in this study. possible. Methods: A prospective study was designed to examine the utility of fibrinogen and monocytes in estimating disease severity in patients with DFU (Diabetic Foot Ulcer). The severity of DFU was assessed using the Wagner criteria distinguishing between patients with diabetic foot without ulcer (WDFU) and with non-infected diabetic foot ulcer (NIDFU) or with infected ulcer (IDFU). In this study the AA also wanted to correlate HbA1c to the concentration of Fibrinogen and the appearance of DFU, as well as the level of lymphocytes and monocyte precursors of macrophages in the evolution of ulcerated and non-ulcerated diabetic feet. Results: Mean blood fibrinogen values were significantly higher in patients with DFU grade ≧2 compared to those with DFU grade ≤1 (424.4±138.8 mg/dL versus 395.3±130.0 mg/dL; p=0.091). Fibrinogen values were correlated with CRP levels, neutrophils, ESR and leukocyte count. Monocytes presented a significant difference between non-diabetic patients with ulcer and without ulcer (0.41 vs 0.29 k/L; p=0.000) and between the diabetic without ulcer (WDFU) and non-diabetic without ulcer (NDWU) groups (0.39 vs 0.29 k/L; p=0.000). The Procalcitonin (PCT) value was <0.5 ng/dl, therefore it had no diagnostic significance. Only 1% of the values found were higher than 0.5 with an average of 1.04 ng/dl (range: 0.52-2.5). Conclusions: Neither monocytes nor HbA1c can be considered biomarkers for the risk of ulcer formation in the diabetic foot, but only as biomarkers of type 2 Diabetes Mellitus. Differently, fibrinogenemia, its pre/post intervention ratio, the  angle and the k value of thromboelastography (TEG), have a clinical significance on the risk of onset and development of ulcerated diabetic foot. The cut-off for ulcer formation for both the pre/post intervention ratio of fibrinogenemia and monocythemia is 1.10, with a sensitivity of 84.1% and a specificity of 24.5% for fibrinogen and 93.8% and 14.8% for monocytes.